2015
DOI: 10.1111/jcmm.12479
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiation of patient‐derived glioblastoma multiforme cell lines results in a cancer stem cell‐like state with mitogen‐independent growth

Abstract: Emerging evidence shows that glioblastoma multiforme (GBM) originates from cancer stem cells (CSCs). Characterization of CSC-specific signalling pathways would help identify new therapeutic targets and perhaps lead to the development of more efficient therapies selectively targeting CSCs. Here; we successfully dedifferentiated two patient-derived GBM cell lines into CSC-like cells (induced glioma stem cells, iGSCs) through expression of Oct4, Sox2 and Nanog transcription factors. Transformed cells exhibited si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 44 publications
(63 reference statements)
2
56
0
1
Order By: Relevance
“…1B). Since neurosphere formation in vitro is correlated with tumor-forming potential of GICs (17), we tested with a self-renewal assay and observed that the combined treatment suppressed sphere formation significantly (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). Since neurosphere formation in vitro is correlated with tumor-forming potential of GICs (17), we tested with a self-renewal assay and observed that the combined treatment suppressed sphere formation significantly (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Immunoblotting was performed as previously described (17). The following antibodies were used for immunoblotting: Bcl-2 (sc-7382), Cyclin A (sc-751), CDK4 (sc-260), CDK6 (sc-177), and mTOR (sc-1549) antibodies were from Santa Cruz, Actin (A5441) and GAPDH (G9545) were from Sigma-Aldrich, and all other antibodies including Cyclin D1 (2978), PARP (9542), phospho-mTOR Ser2448 (2971), phospho-p70 S6K Thr389 (9234), phospho-S6 Ser235/236 (4858), p70 S6K (2708), S6 (2317), phospho-p44/42 Erk1/2 Thr202/Tyr204 (9101), and p44/42 Erk1/2 (9102) as well as antibody array kit (7949) were from Cell Signaling.…”
Section: Methodsmentioning
confidence: 99%
“…Olmez et al 38 recently demonstrated the difficulty of dealing with CSCs by inducing dedifferentiation of patient-derived GBM cell lines into GSC-like cells (induced GBM stem cells, iGSCs) through the expression of Oct4, Sox2, and Nanog transcription factors. The iGSCs formed neurospheres even in the absence of exogenous mitogens, were sensitive to the CSC inhibitor salinomycin, and exhibited resistance to temozolomide (TMZ) therapy.…”
Section: Cancer Stem Cells and Apoptosismentioning
confidence: 99%
“…These transcription factors are found to be over-expressed in several of the cancers and were used to identify cancer stem cell-like cells in glioblastoma [19]. HA-CD44 interaction was proved to activate Nanog which is principally [20] involved in the stem cell maintenance and self-renewal in the ES cells [21,22].…”
Section: Ha Induces the Expression Of Pluripotent Genesmentioning
confidence: 99%